Upaya meningkatkan kemampuan berbicara anak melalui kegiatan berwirausaha jual beli pada kelompok usia 5-6 tahun TK Muslimat NU Masyitoh 19 “Annisa” Jenggot Pekalongan tahun ajaran 2020-2021 - Nanik Utami (Action Research Journal, 2021)
The general objective of this study is to improve the speaking ability of children in the 5-6 years age group totaling 14 children consisting of 9 boys and 5 girls. Muslimat NU Masyitoh 19 “Annisa” Beard Pekalongan obtained by using the method of observation and documentation. The data obtained by observation were analyzed qualitatively by processing data from observations in activities and evaluating children's speaking skills through buying and selling entrepreneurship activities in the form of percentages. The results of this study showed that the results of observations in the 5-6 years age group were initially 14.29%. This was because there was no renewal of learning in children. After improving the action through buying and selling entrepreneurship activities in the classroom using tools and materials in the role center, the results in the first cycle were 57.14% while in the second cycle the buying and selling entrepreneurship activities were by selling agar directly to parents around 85.71 %, This shows an increase in children's speaking skills through buying and selling entrepreneurship activities carried out in cycles I and II in the 5-6 year age group of Muslimat NU Masyitoh 19 "Annisa" Jenggot Kindergarten. Based on all classroom action research activities, it can be concluded that improving the speaking ability of children in the 5-6 year age group TK Muslimat NU Masyitoh 19 "Annisa" Jenggot Ajaran 2020/2021 can be increased through buying and selling entrepreneurship activities. The suggestion that the researcher wants to convey is that educators should increase their knowledge about buying and selling entrepreneurship activities to improve the speaking skills of children in the 5-6 year age group so that learning targets are achieved.